Floral ultraviolet absorbance area responds plastically to ultraviolet irradiance in Brassica rapa - Liberty A. Gray; Sandra Varga; Carl D. Soulsbury (Plant-Environment Interactions, 2022)
Abstract Solar ultraviolet (UV) radiation is known to have significant effects on the development and performance of plants, including flowers. In multiple species, UV‐absorbing floral patterns are associated with environmental conditions such as the solar UV exposure they typically receive. However, it is not known whether plants can increase the UV‐absorbing areas found on petals plastically when in a high‐UV environment. We grew Brassica rapa at three different UV radiation intensities (control, low, and high) and under two exposure duration regimes. We removed petals from flowers periodically during the flowering period and measured the proportion of the petal that absorbed UV. UV‐absorbing areas increased when plants were exposed to longer periods of UV radiation, and at high UV radiation intensities. UV‐absorbing area of petals of the UV intensity treatments decreased over time in long exposure plants. This study demonstrates that flowers can potentially acclimate to different UV radiation intensities and duration of exposure through an increase in UV‐absorbing areas even after a relatively short exposure time to UV. Such a rapid plastic response may be especially beneficial for dynamically changing UV conditions and in response to climate change.